HR 5.0: Digital Transformation of Human Resources in the Age of Artificial Intelligence - Rahmatullah, Reska; Novrianto, Andry; Iskandar, Silvia (SAFE-Network, 2025)
This study examines the transformation of Human Resource Management toward the Human Resources 5.0 paradigm in the context of artificial intelligence adoption. The paper aims to analyze how AI-driven technologies reshape HR functions, managerial practices, and economic value creation while maintaining a human-centered orientation. Using a qualitative conceptual research design, the study relies on secondary data derived from peer-reviewed journal articles, scholarly books, and institutional reports related to artificial intelligence, digital HRM, and organizational performance. The collected data are analyzed through thematic analysis to identify recurring patterns concerning HR performance outcomes, managerial and economic implications, ethical challenges, and strategic alignment. The results indicate that artificial intelligence enhances HR efficiency, decision accuracy, and strategic workforce alignment when integrated within HR 5.0 principles. AI adoption also contributes to cost efficiency and optimized human capital utilization, while introducing challenges related to data privacy, algorithmic bias, and organizational readiness. The study concludes that HR 5.0 represents a holistic transformation that requires balancing technological innovation with ethical governance, managerial capability, and human-centered management. These findings provide conceptual insights for organizations seeking sustainable and responsible HR transformation in the digital era.